Konfirmasi Anopheles sinensis dan Anopheles vagus sebagai Vektor Malaria di Kabupaten Muara Enim Provinsi Sumatera Selatan - Anif Budiyanto; Lasbudi P Ambarita; Milana Salim (Loka Litbang Kesehatan Pangandaran, 2017)
Muara Enim Regency is one of endemic malaria area in South Sumatera Province. The number of malaria clinical cases in 2015 is 9.382 cases with positive confirmed by microscopy is 143 cases (Annual parasite incidence = 0,26 ‰). There were no information or publication confirmed the vector of malaria in this regency. The aims of this study was to confirm species of Anopheles as malaria vector and its biting behavior in Muara Enim Regency. The study carried out two activity that were mosquito collection (indoor and outdoor) starts from 18.00 hours until 06.00 in the morning, and survey of the breeding habitat of pre-adult mosquito. The total of Anopheles mosquitoes collected were 1.443 and 200 mosquitoes were prepared for sporozoit identification by ELISA (enzyme-linked immunosorbent assay) method. Two species of Anopheles (of four mosquitoes), Anopheles sinensis and Anopheles vagus, were confirmed sporozoit positive. Anopheles sinensis tends to bite outdoors while Anopheles vagus prefer indoors. Both species actively biting at 9 p.m. until 4 a.m.